Evaluation of labial and palatal bone thickness of maxillary anterior teeth in prosthodontic treatment planning: Evaluasi ketebalan tulang labial dan palatal gigi anterior maksila pada perencanaan perawatan prostodonsi - Raqib, Abd; Ikbal, Muhammad; Habar, Ike Damayanti; Nurrahma, Rifaat; Sriwulan, Roro Dewiayu; Jubhari, Eri Hendra (Makassar Dental Journal, 2025)
It is necessary to evaluate the labial and palatal bone thickness of maxillary anterior teeth based on gender and age to provide in-formation for prosthodontic treatment planning. This study used an observational design with the Mann-Whitney U statistical test to compare the labial and palatal bone thickness of 6 maxillary anterior teeth between gender (male and female) and age (under and over 30 years old) groups. Measurements were taken at three labial and three palatal points using CBCT. The results showed significant differences in labial bone thickness at several measurement points, with men having significantly greater labial bone thickness than women (p<0.05). Differences in palatal bone thickness according to gender were only seen at one point but were not significant. Individuals under 30 years old showed greater labial and palatal bone thickness than those over 30 years old at certain points (p<0.05). It was concluded that gender affects labial bone thickness more significantly than palatal bone, while in-creasing age plays a role in decreasing bone thickness in both labial and palatal bones. This knowledge can be used for more effective prosthodontic treatment planning.